2021
DOI: 10.3899/jrheum.201005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Valvular Heart Disease in Systemic Sclerosis: An Underrecognized Cardiac Complication

Abstract: Objective Cardiac involvement is a poor prognostic marker in systemic sclerosis (SSc). While diastolic dysfunction, myocardial fibrosis, and arrhythmias are traditionally considered features of primary cardiac involvement in SSc, the incidence of valvular heart disease (VHD) is not well reported. Our objective was to examine the prevalence of VHD at time of SSc diagnosis and incidence of VHD during follow up compared to non-SSc subjects. Methods Medical records of patients with suspicion of SSc were reviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
4
8
0
1
Order By: Relevance
“…Our results agree with the data provided by other population-based studies that have also analyzed the prevalence and/ or incidence of any degree of MAVD in patients with SSc 8,19,[21][22][23][24][25][26][27][28] . The main results of these studies are summarized in Table 5; three studies have not yet been published 25,26,27 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results agree with the data provided by other population-based studies that have also analyzed the prevalence and/ or incidence of any degree of MAVD in patients with SSc 8,19,[21][22][23][24][25][26][27][28] . The main results of these studies are summarized in Table 5; three studies have not yet been published 25,26,27 .…”
Section: Discussionsupporting
confidence: 91%
“…Our results agree with the data provided by other population-based studies that have also analyzed the prevalence and/ or incidence of any degree of MAVD in patients with SSc 8,19,[21][22][23][24][25][26][27][28] . The main results of these studies are summarized in Table 5; three studies have not yet been published 25,26,27 . The great heterogeneity between the studies (discrepancies in study design; lack of control groups in some cases; selection biases, including only patients without clinical manifestations of heart failure; and great variability regarding disease duration) make their results difficult to compare.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is hypothesised that there is an increased frequency of valvular heart disease due to the effects of SSc itself; however, it remains unclear whether the observed increased rates of aortic and mitral valve disease seen in population-based studies [86] are attributable to the increased frequency of screening echocardiograms performed as part of routine SSc care. Case-control studies have suggested an increased frequency of moderate to severe aortic and mitral valvular disease in SSc [87,88]. However, valvular heart disease has not been linked with increased mortality [87] and how valvular pathology may impact SCD risk in SSc is unstudied.…”
Section: Valvular Heart Diseasementioning
confidence: 99%